Building climate-resilient, empowered and food-secure communities: Evidence from gender transformative STIBs in Makueni County - Nchanji, Eileen Bogweh; Ketema, Dessalegn; Njiru, Emerita; Lutomia, Cosmas Kweyu (2025)
Gender-Transformative Socio-Technical Innovation Bundles (GTSTIBs) were piloted in Makueni County to test their effectiveness in strengthening farmers’ resilience and enhancing women’s empowerment. This infographic highlights GTSTIBs adoption trends and potential associations with climate resilience, empowerment indicators, productivity, and food security status. The findings provide evidence of how GTSTIBs can support inclusive and climate-resilient farming systems and informing scaling strategies across program and investment domains at county level.